"Bid vir my ma" : a narrative inquiry into the experiences of white Christian Afrikaner females during SADF conscription from 1980 until 1990 - O'Connell, Siona (University of Pretoria, 2020)
Dissertation (MSocSci)--University of Pretoria, 2019.